Archives - Lison, Andrew; Mars, Marcell; Medak, Tomislav; Prelinger, Rick (In Search of Media, 2019)
Archives have become a nexus in the wake of the digital turn. This book sets out to show how expanded archival practices can challenge contemporary conceptions and inform the redistribution of power and resources. Calling for the necessity to reimagine the potentials of archives in practice, the three contributions ask: Can archives fulfill their paradoxical potential as utopian sites in which the analog and the digital, the past and future, and remembrance and forgetting commingle?